Capital structure and profitability in Malaysian plantation sector - Sek, Wen Jie (Universiti Malaysia Sarawak (UNIMAS), 2015)
This purpose of this study is to examine the relationship between the capital structure and profitability of 21 plantation companies which listed in Bursa Malaysia during the years 2009 to 2013. The dependent variable is firms’ profitability, measured by Return on assets (ROA). Independent variables in this study include Debt to assets ratio (DAR), Debt to equity ratio (DER), Firms’ growth (G), Liquidity (LQ), Assets tangibility (TANG) and Degree of operating leverage (DOL). Panel data regression analysis is utilized to analyze on the findings of the study. The result shows that Debt to equity ratio (DER) and Degree of operating leverage (DOL) are positive and significantly related to ROA, while Debt to assets ratio (DAR), Firms’ growth (G), Liquidity (LQ) and Assets tangibility (TANG) are found to be negative and significantly related to ROA.